Development of piezoelectroluminescent and magnetostriction detectoscopy methods of aviation polymer composition materials with diagnostic piezoactive particles for location and of defects visualization - Pankov, A.A.; Pisarev, P.V.; Shobey, M.M. (Perm Federal Research Centre Journal, 2019)
The new piezoelectroluminescent optical fiber sensors are developed for integration into composite structures for the purpose of specified diagnosing and monitoring spatial distributed scalar and tensor physical and mechanical fields, in particular, the temperature, pressure and volumetric deformed state in the loaded composite designs by processing results of intensities for integrated mono or multi-colour light signals at the exit of the sensor fiber. New schemes of the functioning and numerical processing algorithms of informative integrated light signals at the exit of optical fiber sensors were developed. The informative light signal appears as a result of «mechanoluminescent effect» by interaction of piezoelectric and electroluminescent of the sensor layers. Light signals are transmitted via optical fiber to a «receiver analyzer»; control electric signals on the electrodes allow to find locations of heterogeneities of diagnosed fields along the length of the sensor. Results of numerical modeling the «scanned» real distributions and its density functions of the diagnosed fields along the length of sensors are presented; density functions are solutions of the Fredholm integral equation of the 1st kind with the use of the new developed processing algorithms of informative integrated light signals at the exit of the optical fiber.